Sistem Pakar Menggunakan Metode Certainty Factor Dalam Akurasi Identifikasi Jenis Penyakit alergi Kulit Pada Balita - Nia Nofia Mitra; Gunadi Widi Nurcahyo (Jurnal Informasi dan Teknologi, 2020)
The immune system possessed by toddlers who are weaker than adults makes toddlers more susceptible to diseases, including allergic diseases. Allergy is a hypersensitivity reaction that can be seen by immunologists, which can affect almost all body tissues and clinical symptoms according to the affected organs, allergies usually occur in human skin. The skin is the largest organ of the human body, which is the body's first defense against bacteria and viruses. For this reason, parents must pay more attention to toddlers because poor health conditions will certainly greatly affect the child's growth. Lack of experts in the field of skin so we need an expert system that is able to match the experts in the hope that it can help parents to know about skin allergies in toddlers early. The method used to identify the type of skin allergic disease in toddlers is using the Definty Factor method where the CF method shows the certainty value of an uncertain fact and reaches a 100% accuracy level from testing 8 patient data, so that the Definty Factor method can be used to see the types of skin diseases suffered by toddlers.